Cost Effectiveness of Endovascular Revascularisation vs. Exercise Therapy for Intermittent Claudication Due to Iliac Artery Obstruction. (March 2022) - van Reijen, Nick S.; van Dieren, Susan; Frans, Franceline A.; Reekers, Jim A.; Metz, Roderik; Buscher, Hessel C.J.L.; Koelemay, Mark J.W.; ,; Legemate, D.A.; Idu, M.M.; Balm, R.; Reekers, J.A.; et al.
Abstract : Objective: To compare cost effectiveness of endovascular revascularisation (ER) and supervised exercise therapy (SET) as primary treatment for patients with intermittent claudication (IC) due to iliac artery obstruction. Methods: Cost utility analysis from a restricted societal perspective and time horizon of 12 months. Patients were included in a multicentre randomised controlled trial (SUPER study, NCT01385774, NTR2648) which compared effectiveness of ER and SET. Health status and health related quality of life (HRQOL) were measured using the Euroqol 5 dimensions 3 levels (EQ5D-3L) and VascuQol-25-NL. Incremental costs were determined per allocated treatment and use of healthcare during follow up. Effectiveness of treatment was determined in quality adjusted life years (QALYs). The difference between treatment groups was calculated by an incremental cost utility ratio (ICER). Results: Some 240 patients were included, and complete follow up was available for 206 patients (ER 111, SET 95). The mean costs for patients allocated to ER were €4 031 and €2 179 for SET, a mean difference of €1 852 (95% bias corrected and accelerated [bca] bootstrap confidence interval 1 185 – 2 646). The difference in QALYs during follow up was 0.09 (95% bcaCI 0.04 – 0.13) in favour of ER. The ICER per QALY was €20 805 (95% bcaCI 11 053 – 45 561). The difference in VascuQol sumscore was 0.64 (95% bcaCI 0.39 – 0.91), again in favour of ER. Conclusion: ER as a primary treatment, results in slightly better health outcome and higher QALYs and HRQOL during 12 months of follow up. Although these differences are statistically significant, clinical relevance must be discussed due to the small differences and relatively high cost of ER as primary treatment.